The Effect of Financial Literacy, Financial Attitude, and Digital Transaction Adoption on MSME Financial Management in the F&B Sector in Pontianak - Salsa Seprilla Rizki; Heni Safitri; Dedi Hariyanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
Abstract This study aims to analyze the effect of financial literacy, financial attitude, and digital transaction adoption on the financial management of micro, small, and medium enterprises (MSMEs) in the food and beverage (F&B) sector in Pontianak City. This study employs a quantitative approach with an associative research design. The sampling technique used is purposive sampling, involving 150 MSME owners as respondents. Primary data were collected through a questionnaire using a five-point Likert scale and were analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The results show that financial literacy has a positive and significant effect on MSME financial management, financial attitude has a positive and significant effect, and digital transaction adoption also has a positive and significant effect. Simultaneously, the three independent variables have a significant effect on MSME financial management. The correlation coefficient indicates a strong relationship (R = 0.722) with a coefficient of determination of 0.521, meaning that 52.1% of the variation in MSME financial management can be explained by financial literacy, financial attitude, and digital transaction adoption, while the remainder is influenced by other factors outside the research model. These findings emphasize the importance of improving financial literacy and financial attitude as well as utilizing digital transactions in supporting more effective and sustainable financial management for F&B MSMEs.